Improving the Ability of Smkn 1 Bukittinggi Students Majoring in Geomatics Engineering to Use the Global Navigation Satellite System (GNSS) - Pertiwi, Mentari Dian; Putri, Sri Kandi; Jaya, Wikan (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to improve the skills of GNSS usage by students in Geomatics Engineering Department of SMKN 1 Bukittinggi. Training on the use of GNSS will be conducted using the latest GNSS device owned by the school. The students will be taught about the operation and programming of GNSS devices, as well as methods of analyzing the data generated. After the training, the students will be evaluated through tests and field projects. The results show that most students initially have a limited understanding of GNSS and difficulty in using GNSS devices. The improvement of this ability has positive implications for the preparation of students in facing the increasingly complex demands of the job market. The ability to use GNSS is becoming more important in various fields such as construction, mapping, surveying, precision agriculture, and environmental monitoring. Students who have been well trained in the use of GNSS will have a competitive advantage in seeking employment or pursuing further education.